A novel method of strain - bending moment calibration for blade testing. Issue 4 (September 2016) - Greaves, P; Prieto, R; Gaffing, J; van Beveren, C; Dominy, R; Ingram, G
Abstract: A new method of interpreting strain data in full scale static and fatigue tests has been implemented as part of the Offshore Renewable Energy Catapult's ongoing development of biaxial fatigue testing of wind turbine blades. During bi-axial fatigue tests, it is necessary to be able to distinguish strains arising from the flapwise motion of the blade from strains arising from the edgewise motion. The method exploits the beam-like structure of blades and is derived using the equations of beam theory. It offers several advantages over the current state of the art method of calibrating strain gauges.